Teologi Kesejahteraan Dan Keadilan Sosial Dalam Islam - A. Zaeny; Nofrizal, Nofrizal; Sucitra Aprilia (Indonesian Journal of Islamic Theology and Philosophy, 2026)
Abstract; This study examines the concept of welfare theology and social justice in Islam, and its relevance as a critical and constructive framework in addressing the failures of modern development paradigms. The problem addressed is the tendency of contemporary development to prioritize material growth while neglecting moral, spiritual, and distributive justice dimensions. This research employs a qualitative approach with normative-descriptive and library research methods, drawing primarily on classical and contemporary Islamic thought by scholars such as Nurcholish Madjid, M. Amien Rais, Kuntowijoyo, and Abdurrahman Wahid, supplemented by relevant international academic journals. The findings reveal that welfare theology in Islam is grounded in the principle of tawhid, which places God as the ultimate source of value guiding all aspects of social life. Social justice (ʿadl), balance (mīzān), and brotherhood (ukhuwah) are identified as the foundational pillars of Islamic development ethics. The novelty of this research lies in its systematic synthesis of welfare theology as an integrated normative framework that can serve as an alternative to secular development paradigms, demonstrating that instruments such as zakat, prohibition of riba, and Islamic public policy are not merely ritual obligations but strategic tools for social transformation. This study contributes to the discourse on Islamic economics and social theology, particularly in the Indonesian context, by offering a theologically grounded model of just and humane development. Keywords: Islam; Social Justice; Welfare Theology.   Abstrak; Penelitian ini mengkaji konsep teologi kesejahteraan dan keadilan sosial dalam Islam serta relevansinya sebagai kerangka kritis dan konstruktif dalam menyikapi kegagalan paradigma pembangunan modern. Permasalahan yang diangkat adalah kecenderungan pembangunan kontemporer yang memprioritaskan pertumbuhan material seraya mengabaikan dimensi moral, spiritual, dan keadilan distributif. Penelitian ini menggunakan pendekatan kualitatif dengan metode normatif-deskriptif dan studi kepustakaan (library research), bersumber pada pemikiran Islam klasik dan kontemporer dari para tokoh seperti Nurcholish Madjid, M. Amien Rais, Kuntowijoyo, dan Abdurrahman Wahid, yang dilengkapi dengan jurnal-jurnal akademik relevan. Hasil penelitian menunjukkan bahwa teologi kesejahteraan dalam Islam berakar pada prinsip tauhid yang menempatkan Tuhan sebagai sumber nilai tertinggi yang mengarahkan seluruh aspek kehidupan sosial. Keadilan (ʿadl), keseimbangan (mīzān), dan persaudaraan (ukhuwah) diidentifikasi sebagai pilar utama etika pembangunan Islam. Novelty penelitian ini terletak pada sintesis sistematis teologi kesejahteraan sebagai kerangka normatif terpadu yang dapat menjadi alternatif paradigma pembangunan sekuler, dengan membuktikan bahwa instrumen seperti zakat, larangan riba, dan kebijakan publik Islami bukan sekadar kewajiban ritual, melainkan alat transformasi sosial yang strategis. Penelitian ini berkontribusi pada diskursus ekonomi Islam dan teologi sosial, khususnya dalam konteks Indonesia, dengan menawarkan model pembangunan berkeadilan yang berbasis teologi. Kata Kunci: Islam; Keadilan Sosial; Teologi Kesejahteraan,